Rediscovering Apprenticeship
XX, 175 p.
Keywords: The rediscovery of the value of apprenticeships has been one of the most significant trends in vocational education in recent years, and has prompted an array of research and development projects in countries around the world. In this volume, the renewed interest in the apprenticeship tradition and the various steps towards the implementation of innovative apprenticeship programmes are analysed and discussed from different perspectives. Beginning with a number of chapters that describe recent developments in apprenticeship training in different national contexts, the book moves on to analyze the way in which both the quality and profitability of apprenticeship act in concert as the most influential drivers of innovation in this field. In sum, this book makes an important contribution to the international literature on apprenticeship. It draws together some of the leading researchers in the area, and with its overview of a number of national Vocational Education and Training (VET) projects, provides a body of knowledge on current practices and issues that has previously been lacking in this complex interdisciplinary field. The lessons learned from countries’ experiences, as presented in this book, provide a valuable platform for policy-makers and scholars alike.